Research on the Path to Enhancing the Guidance Ability of College Normal Students for Study Tours under the New Employment Forms - Wei Mo; Yifei Dong; Yuhua Xie (Education Research on Study Tours and Practice, 2026)
Under the background of new employment forms, study tours have become an important part of the basic education curriculum system. As “study tour guides”, college normal students’ participation in study tours not only expands the platform for educational practice but also puts forward higher requirements for their comprehensive quality and educational ability. This study explores the problems and causes existing in the study tour guidance ability of college normal students from the dimensions of role cognition, ability preparation, practical challenges and support needs, and proposes improvement paths， with the aim of providing theoretical basis and practical guidance for the construction mechanism of applied and compound collaborative education in normal universities, improving the training mechanism of study tour guides, and providing guarantee strategies for enhancing the quality and safety of local study tours.